Eufemisme dalam Bahasa Iban: Satu kajian kes di Kampung Lebor, Serian, Sarawak - Mohammad Shahrul Nizam, Abd Wahid (Universiti Malaysia Sarawak, (UNIMAS), 2017)
This study is to determine the existence of euphemism in the Than language, in Kampung Lebor, Serian, Sarawak based on the theories by Allan & Burridge (1991). The main objective is to (i) identify the euphemistic expressions in the Than language, (ii) to determine the frequency of the usage of euphemism among the Than community based on their age and (iii) to investigate the factors that influence the use of euphemism in the Than community. The methods used are interviews and questionnaires involving a man and a woman aged 50 and above, who speaks fluent Than. Next, questionnaires were distributed to 105 respondents of different ages. The findings show that there were nine types of euphemism in the Kampung Lebor Than community. They include (1) body parts, (2) sex, (3) gender involving masculinity and femininity, (4) anger, (5) hate, (6) illnesses, (7) death, (8) fear oriented by animals and spirits, and finally (9) God or religion. The findings from the questionnaires showed that there was an age gap in the usage of euphemism, in which the younger Than community in Kampung Lebor do not use as much euphemism in their daily conversations as compared to the older ones. The main factor in the usage of euphemistic expressions in the Than community in Kampung Lebor is caused by the influence of customs and beliefs, which were used and passed down for generations.